HBeAg testing is better than quantitative HBsAg assay as an alternative to HBV DNA assay among HBV-infected pregnant women - Nguyen, Minh Ngoc; Nguyen, Thi Thu Huong; Pham, Tran Dieu Hien; Khuu, Van Nghia; Hoang, Quoc Cuong; Nguyen, Vu Thuong; Tran, Ngoc Huu (The Journal of Infection in Developing Countries, 2023)
Introduction: Using tenofovir disoproxil fumarate (TDF) is recommended in the 3rd trimester for pregnant women with HBV DNA ≥ 200,000 IU/mL to prevent mother-to-child transmission (MTCT) of hepatitis B virus (HBV). However, HBV DNA quantification is unavailable in many resource-limited areas worldwide, hence prophylaxis is often missed. The aim of this study was to determine whether HBeAg or qHBsAg is a better alternative to HBV DNA testing in HBV-infected pregnant women. Methodology: In this prospective cohort study, pregnant women with HBV infection were recruited in 3 hospitals from October 2019 to November 2020. Socio-demographic and clinical data were collected. Blood samples were taken for qHBsAg and HBV DNA testing. HBeAg results were collected from the medical records of the participants who visited a doctor during the study. Results: 465 pregnant women met the study criteria. 41.9% were HBeAg positive, 33.3% had high qHBsAg levels (> 104 IU/mL), 38.3% had high HBV DNA levels (≥ 200,000 IU/mL). Pregnant women with high qHBsAg levels were 27 times more likely to have high HBV DNA levels (aOR = 27.0, 95% CI: 11.1-65.5, p < 0.001). Participants who were HBeAg positive were 57.5 times more likely to have high HBV DNA levels (aOR = 57.5, 95% CI: 23.0-140.0, p < 0.001). The sensitivity of qHBsAg and HBeAg was 80% and 94%, respectively; and specificity was 95% and 90%, respectively. Conclusions: HBeAg testing should be considered over qHBsAg assay as an alternative to HBV DNA assay because of its technical simplicity, lower cost, and fewer missed treatments.